Identification and typification of Nepenthes blancoi, with N. abalata sp. nov. from the western Visayas, Philippines. (25th January 2013) - Cheek, Martin; Jebb, Matthew
Abstract : Nepenthes blancoi Bl. is neotypified on material conspecific with N. alata Blanco. Material previously associated with N. blancoi is described as N. abalata Jebb & Cheek sp. nov. This is a grassland species seemingly related to N. philippinensis Macfarl. but with similarities to the grassland species of Indo‐China. Its conservation status is assessed as 'Critically Endangered' (CR).